Penegakan Hukum Terhadap Anak Sebagai Korban Praktik Eksploitasi Seksual di Kota Makassar - Ningsih, Irma Wati; Musakkir, Musakkir; Heryani, Wiwie (Al-Mizan (e-Journal), 2024)
This study aims to evaluate and find forms of legal protection and factors that affect law enforcement against children as victims of sexual exploitation practices in Makassar City. This research is empirical legal research using a statutory approach. Data were analyzed using descriptive qualitative analysis. The results of this study indicate that: (1) the form of legal protection against children follows Law Number 35 of 2014 concerning Child Protection which provides children's rights in the form of legal assistance, rehabilitation, and prevention; (2) Factors affecting law enforcement against child victims of sexual exploitation practices in Gorontalo City are legal substance factors, law enforcers, facilities, society, and legal culture. All of them have not been run optimally by the laws and regulations.